Alterations in Serum Biochemical Parameters in Response to Gasoline Inhalation and the Protective Effects of Green Tea and Curcumin - Elsayed, Ata Sedik Ibrahim (Pakistan Journal of Nutrition, 2015)
Herbal medicines derived from plant extracts are being increasingly utilized to treat a wide variety of clinical disease. More attention has been paid to the protective effects of natural antioxidants against drug-induced toxicities especially whenever free radical generation is involved. Flavonoids have been found to play important roles in the non-enzymatic protection against oxidative stress, especially in case of cancer. This study aimed to investigate the alterations in biochemical parameters in serum which measure liver functions, kidney functions, serum lipids and proteins due to inhalation of gasoline and the protective effects of some natural products against gasoline toxicity. Green tea extract and powdered curcumin were chosen as antitoxicity natural products. CD1 mice were taken as experimental model. Mice were exposed to gasoline vapor 2 h/day for 3 weeks in inhalation chamber. The concentration of gasoline is 9375 ppm and the concentration of benzene is 100 fold less than gasoline in equilibrium with pure benzene being 93.75 ppm. The results concluded that: 1-Liver functions did not affect in all animal groups. 2-Increase in globulin concentration in serum was observed in gasoline group, this was lowered in the other groups. 3-Triglycerides in serum were increased by gasoline and returned near to normal control by green tea extract and curcumin addition to diet. 4-Growth rate per day was reduced with gasoline inhalation and ameliorated with curcumin, but hepatosomatic and spleenosomatic indices were not affected in all groups.